Rabassa and the “Narrow Act”: Between Possibility and an Ethics of Doubt - Guzmán, María (TTR, 2008)
AbstractIn this article I examine the writings about translation by Gregory Rabassa, translator into English of such canonical novels as Gabriel García Márquez’s Cien años de soledad and Julio Cortázar’s Rayuela. I look at some of Rabassa’s articles about translation and at his recently published book If This Be Treason: Translation and Its Dyscontents, in light of contemporary approaches in translation studies that conceptualize the translator and translators’ self-images and representations. I examine the conceptions of language and translation that underlie Rabassa’s statements in general, and look at them in light of Lawrence Venuti’s idea of the translator’s self-effacement. I discuss the way in which translators’ ideas about translation in general and about their own practice in particular can inform conceptualizations about the figure and status of the translator.